FREQUENCY OF HASHIMOTO THYROIDITIS IN PAPILLARY THYROID CANCER PATIENTS AND ITS IMPACT ON THEIR OUTCOME - Batool, Sumera; Das, Bhagwan; Arif, Muhammad; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2022)
Background: Hashimoto thyroiditis (HT) is an autoimmune disorder of thyroid gland and is the most common cause of hypothyroidism. Its association with thyroid lymphoma is well established but with papillary thyroid cancer (PTC), the studies have shown inconsistent results. Methods: It is a retrospective review of papillary thyroid cancer patients and 213 participants were included for final analysis. They were divided in two groups, based on presence or absence of Hashimoto thyroiditis. We noted their demographic details, histopathological diagnosis, presence of thyroid autoantibodies, TNM staging, outcome and duration of follow up. Results: The frequency of Hashimoto thyroiditis in papillary thyroid cancer patients was found to be 34.27% (73). In Hashimoto thyroiditis and PTC patients, more patients were in T1 and T2 stage i.e., 27.4% and 38.4% as compared to PTC alone group, who had more patients with T3 and T4 disease 44.3% and 5% respectively. Although lymph node metastasis was more common in PTC with Hashimoto thyroiditis 56.2%, but distant metastasis was observed more in isolated PTC group 14.3%. Cure was observed in 75.3% and 47.1% in PTC patients with and without Hashimoto thyroiditis respectively. While 22.9% patients having isolated PTC had persistent disease as compared to 6.8% when PTC was accompanied with Hashimoto thyroiditis. Conclusion: The papillary thyroid cancer patient who had concomitant Hashimoto thyroiditis, had a less aggressive disease in terms of T stage and distant metastasis and they had a better outcome in terms of higher cure rate and less persistent disease as compared to the papillary thyroid cancer without Hashimoto thyroiditis.